Microsoft Visual Basic 2010 - Halvorson, Michael; Halvorson, Michael (Redmond, Washington : Microsoft Press, 2010)
Teach yourself the fundamentals of working with Visual Basic 2008$1 (Bone step at a time. With STEP BY STEP, you work at your own pace through hands-on, learn-by-doing exercises. Whether you$1 (Bre a beginning programmer or new to this specific language, you$1 (Bll understand the core capabilities and fundamental techniques for Visual Basic 2008$1 (Band rapidly build robust, elegant applications. Each chapter puts you to work, showing you how, when, and why to use the latest features of Visual Basic$1 (Bguiding you each step of the way as you create actual components and working applications for Windows. You$1 (Bll also explore data management and Web-based development topics. PLUS$1 (Bget practice files with sample code and data sets on the companion CD.s
Keywords: VISUAL BASIC (COMPUTER PROGRAM LANGUAGE)